Developing "EMBER": A Fantasy Puzzle Adventure Game with An Approach to Agile by Applying Game-Scrum Methodology - Aisha Gemala Jondya; Hisyam Izuddin Anwar; Muhammad Rifky Hermawan; Tobia Azaria Deru (Engineering, MAthematics and Computer Science (EMACS) Journal, 2022)
Digital games development process is often done using traditional methods. Many digital game developers believe that the game development process cannot be equated and use other software development methods because game development is not only focused on technical processes such as programming and coding but also creative processes such as asset and display design. In this study, the process of developing a fantasy adventure puzzle game was carried out using the Game-Scrum approach, a method modified from the Agile Scrum method. As well as the software development process using the agile method, game development using this method is carried out with an iterative process where each process allows an update of the feedback given to each sprint backlog. At the end of the study it was concluded that although there were still some things that had to be adjusted, basically the Game Scrum method could be adapted for the development of a digital game.